2010
DOI: 10.1104/pp.110.160424
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Functions as a Signal and Acts Upstream of AtCaM3 in Thermotolerance in Arabidopsis Seedlings    

Abstract: To characterize the role of nitric oxide (NO) in the tolerance of Arabidopsis (Arabidopsis thaliana) to heat shock (HS), we investigated the effects of heat on three types of Arabidopsis seedlings: wild type, noa1(rif1) (for nitric oxide associated1/resistant to inhibition by fosmidomycin1) and nia1nia2 (for nitrate reductase [NR]-defective double mutant), which both exhibit reduced endogenous NO levels, and a rescued line of noa1(rif1). After HS treatment, the survival ratios of the mutant seedlings were lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 54 publications
6
102
1
Order By: Relevance
“…To investigate whether the activation is due to NO produced via the NR or AtNOA1 pathways, we studied Cd 2+ -dependent SnRK2 activation in hydroponically grown seedlings of nia1nia2 (double knockout mutant of NR) and atnoa1 Arabidopsis T-DNA insertion mutants. The atnoa1 and nia1nia2 mutants had previously been shown to produce less NO in response to several biotic as well as abiotic stresses (Besson-Bard et al, 2008;Zhao et al, 2009;Hao et al, 2010;Lozano-Juste and León, 2010;Sun et al, 2010;Xuan et al, 2010). In both nia1nia2 and atnoa1 seedlings, we observed activation of SnRK2(s) in response to CdCl 2 treatment (Fig.…”
Section: Ntosak Undergoes Activation In Tobacco Cells In Response To mentioning
confidence: 50%
“…To investigate whether the activation is due to NO produced via the NR or AtNOA1 pathways, we studied Cd 2+ -dependent SnRK2 activation in hydroponically grown seedlings of nia1nia2 (double knockout mutant of NR) and atnoa1 Arabidopsis T-DNA insertion mutants. The atnoa1 and nia1nia2 mutants had previously been shown to produce less NO in response to several biotic as well as abiotic stresses (Besson-Bard et al, 2008;Zhao et al, 2009;Hao et al, 2010;Lozano-Juste and León, 2010;Sun et al, 2010;Xuan et al, 2010). In both nia1nia2 and atnoa1 seedlings, we observed activation of SnRK2(s) in response to CdCl 2 treatment (Fig.…”
Section: Ntosak Undergoes Activation In Tobacco Cells In Response To mentioning
confidence: 50%
“…Nitric oxide (NO) is a bioactive molecule that is extensively involved in plant defenses against environmental stimuli, including drought, salt, cold, heat, and disease (Zhao et al, 2004;Guo and Crawford, 2005;Neill et al, 2008;Wilson et al, 2008;Xuan et al, 2010). NO is mainly produced via two pathways: the Arg-dependent nitric oxide synthase (NOS) and nitrite-dependent nitrate reductase (NR) pathways.…”
mentioning
confidence: 99%
“…[8][9][10] Yet, the overexpression of HSPs, so called the heat shock response (HSR), can be activated under mild physiological conditions that are unlikely to cause any protein denaturation in the cell. [11][12][13] Although multiple HSR triggering mechanisms may co-exist, 6,[14][15][16] recent evidences in bacteria, algae, plants and mammalian cells point at the understanding how plants sense and respond to heat stress is central to improve crop tolerance and productivity. recent findings in Physcomitrella patens demonstrated that the controlled passage of calcium ions across the plasma membrane regulates the heat shock response (hSr).…”
mentioning
confidence: 99%